The effect of phenotype color of local chicken feathers on production traits (Journal of Hama University, 2026)
Local hen's chicks (light brown, light wheat, sugar white) were cared for in a battery in an open barn. The results indicate that the age of sexual maturity was significantly earlier for the light brown feathered and light wheaten feathered hens by 8 days and 5 days, respectively, compared to the sugar white feathered hens. The average egg production of the hen was not affected by the phenotypic trait of feather color during the experimental period from 21 weeks to 37 weeks of age. The production of the hen was 0.80 eggs/day for the light brown feathered hens, 0.79 eggs/day for the light wheaten feathered hens, and 0.80 eggs/day for the sugar white feathered hens. Egg weight increased (statistically reliable) by 2.2 g and 2.5 g for light brown and light wheaten-feathered hens, respectively, compared to egg weight for sugar white-feathered hens. within 28 days the feed intake (significant) for the light-brown hens increased by 0.1 kg/hen and 0.2 kg/hen compared to light-colored wheaten hens, and hens with sugar white feathers, The feed intake increased (significant) for light-colored wheaten hens by 0.1 kg/hen compared to hens with sugar white feathers. The consumption of feed to produce one egg for sugar white-feathered hens decreased (significant) by 5g and 7g compared to the amount of feed intake by light-colored brown hens and light-colored wheat-colored hens. The phenotype color character of the hens did not affect the amount of feed intake to produce one kilogram of eggs, the differences between hens of different colors were not significant. The mass of eggs (significant) produced by light brown hens increased (5.34 kg/ hen) compared to light-colored wheat hens (5.28 kg/hen) and sugar white hens (5.11 kg/hen). The percentage of eggs pecked by the hen’s hooves was also not affected. The percentage of eggs perforated through the hen's fingernail is 3.47%, 2.38%, and 3.21% for brown light-colored hens, light-colored wheaten hens, and sugar white-colored hens.